Parents' experiences of information-seeking and decision-making regarding complementary medicine for children with autism spectrum disorder: a qualitative study - Caroline A. Smith; Chloe Parton; Marlee King; Gisselle Gallego (BMC, 2020)
Abstract Background Complementary and alternative medicine and therapies (CAM) are widely used by parents of children with autism spectrum disorder (ASD). However, there is a gap in our understanding of how and why parents of children with ASD make decisions about CAM treatment, and how "evidence" influences their decision-making. The aim of this study was to explore views and perspectives on CAM decision-making among parents of children with ASD in Australia. Methods Semi-structured interviews were conducted with parents of children with ASD (18 years and under) who were living in Australia. The interviews were digitally recorded, transcribed and then analysed using thematic analysis. Results Twenty-one parents were interviewed (20 women and one man). The mean age of participants was 43 years, (SD = 5.12 years), the majority of whom were born in Australia (71%), and almost half (43%) had a bachelor degree or higher. Three main themes were identifiedin the thematic analysis. First theme was 'Parents' experiences of researching CAM treatments, the second theme was, "Navigating CAM information and practices", which comprises of the subthemes: Assessing information on CAM treatments' What counts as 'evidence'? and Assessing the impact of CAM treatments on the child - What counts as effective?, and the final theme was, "Creating a central and trustworthy source about CAM". Across themes parents' CAM decision-making was described as pragmatic, influenced by time, cost, and feasibility. Parents also reported that information on CAM was complex and often conflicting, and the creation of a centralised and reliable source of information on CAM was identified as a potential solution to these challenges. Conclusion The development of evidence-based information resources for parents and supporting CAM health literacy may assist with navigating CAM decision-making for children's with ASD.